2017
DOI: 10.1080/17408989.2017.1342789
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical principles of learning to teach meaningful physical education

Abstract: Background: Concerns that current forms of physical education teacher education (PETE) are not adequately providing teachers with the tools necessary for working with the realities and challenges of teaching physical education in contemporary schools has led some scholars to advocate for an approach that prioritises meaningfulness in physical education. There is, however, little empirical evidence of how future teachers might be taught to facilitate meaningful physical education experiences. Purpose: This pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 35 publications
1
62
0
3
Order By: Relevance
“…The pedagogical principles guiding the lesson planning in the IG's PE program were inspired by Chróinín, et al [34], and were divided into five key points: (i) promote social interaction with a positive participation among students; (ii) stimulate and involve students in activities which are suitable for them (neither too difficult, nor too easy); (iii) increase motor competence by involving opportunities for motor learning and fitness improvement during each activity and by providing information and engaging in reflection about physical exercises usefulness and their practice outside the school context; (iv) develop a positive, fun and enjoyable setting based on satisfaction in improving and learning new skills; (v) experience a pleasant experience during PE lessons as a result of a positive children's engagement and commitment (mastery climate).…”
Section: Methodsmentioning
confidence: 99%
“…The pedagogical principles guiding the lesson planning in the IG's PE program were inspired by Chróinín, et al [34], and were divided into five key points: (i) promote social interaction with a positive participation among students; (ii) stimulate and involve students in activities which are suitable for them (neither too difficult, nor too easy); (iii) increase motor competence by involving opportunities for motor learning and fitness improvement during each activity and by providing information and engaging in reflection about physical exercises usefulness and their practice outside the school context; (iv) develop a positive, fun and enjoyable setting based on satisfaction in improving and learning new skills; (v) experience a pleasant experience during PE lessons as a result of a positive children's engagement and commitment (mastery climate).…”
Section: Methodsmentioning
confidence: 99%
“…As indicated initially, I see hope for physical education in, for example, activist, appreciative, paradoxical and participatory approaches (Enright, Hill, Sandford, & Gard, 2014;Enright & O'Sullivan, 2010;Larsson et al, 2014;Luguetti et al, 2017;Oliver & Hamzeh, 2010;Oliver & Kirk, 2016). Other apt examples are the work on meaningful physical education (Fletcher, Ní Chróinín, Price, & Francis, 2018;Ní Chróinín, Fletcher, & O'Sullivan, 2018), social justice (Azzarito, Macdonald, Dagkas, & Fisette, 2017), or pedagogical cases such as those introduced by Armour (2014). But also at a policy level in Australia and Scotland, new curricula show promise (Carse, Jess, & Keay, 2018;Jess, Atencio, & Thorburn, 2011;Macdonald, 2013;McCuaig, Quennerstedt, & Macdonald, 2013;Thorburn, 2017;Thorburn & Horrell, 2014).…”
Section: A Focus On the Art Of Teachingmentioning
confidence: 99%
“…On the other hand, it has been suggested that the PE teacher is not receiving adequate tools to face contemporary challenges in the school environment [45]. This can be observed in many items of the present study, where PE professionals and students blame the lack of continuing education opportunities.…”
Section: What Determine the Choices Of The Contents Of The Physical Ementioning
confidence: 61%